BAHAN AJAR BALAGHAH PADA PRODI PBA STAIN JURAI SIWO METRO DALAM MENINGKATKAN PRESTASI BELAJAR MAHASISWA (Suatu Analisis Kelayakan) - Khoirurrijal, Khoirurrijal (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2015)
AbstractBalaghah is regarded as a difficult subject matter by the students of Arabic Departement of STAIN Jurai Siwo Metro. The difficulty is due to a lot of various factors, one of them is the using of Arabic books published be Middle East schools. The title of the research: Teaching Balaghah on Arabic Language Education Program of STAIN Jurai Siwo Metro in Improving Student Achievement (A Feasibility Analysis)â. This research is aimed at understanding and analyzing: (a) The balaghoh subject on Arabic Departement of STAIN Jurai Siwo Metro; (b). The learning achievement of Balaghoh Subject of students of Arabic Departement of STAIN Jurai Siwo Metro; (c). The effect Instructional Materials Balaghoh feasibility study on student achievement of Arabic Departement ofÂ STAIN Jurai Siwo Metro. Before distributing the data, validity and reliability tests were carried out; the data obtained were processed with the computer program SPSS (Statistical Program for Social Science) version 16.0 with a 95 % significance level (Î±= 5 %). As for testing the researchers hypothesis using Simple Linear Regression Test. The results showed: (a). Balaghoh Subject of the Arabic Departement of STAIN Jurai Siwo Metro was feasible for use. This was indicated by a score of an average value of 47.2; (b). Student Achievement of Balaghoh of Arabic Departement of STAIN Jurai Metro Siwo was average height with an average score of 43.5, and (c). There was a significant relationship between Instructional Materials Balaghoh Feasibility study on student achievement of Arabic Departement of STAIN Jurai Siwo Metro. It was shown in the results of the correlation between variables X and Y, the value obtained was 0.892 means a significant difference between the feasibility Balaghoh teaching materials with improved student achievement of Arabic Departement of STAIN Jurai Siwo Metro.Keywords: Balaghah teaching materials, and learning achievement.